Crop and weed discrimination using Laws’ texture masks - Kamath, Radhika; Balachandra, Mamatha; Prabhu, Srikanth (International Journal of Agricultural and Biological Engineering, 2020)
Computers have become an integral part of human lives. Computers are used in almost every field even in agriculture. Technologies like computer vision-based pattern recognition are being used to detect diseases and pests like weeds affecting the crop. The Weeds are unwanted plants growing among crops competing for nutrients, water, and sunlight. It can significantly reduce the quality and yield of the crops incurring a huge loss to the farmers. This paper investigates the use of texture features extracted from Laws’ texture masks for discrimination of Carrot crops and weeds in digital images. Laws’ texture method is one of the popular methods used to extract texture features in medical image processing, though not much explored in plant-based images or agricultural images. This experiment was carried out on two categories of benchmark digital image datasets of Carrot crop and Carrot weed respectively, which are publicly available. A total of 70 texture features were extracted. The dimensionality reduction technique was used to get the optimal features. These features were then used to train the Random Forest classifier. The results and observations from the experiment showed that the classifier achieved above 94% accuracy. Keywords: precision agriculture, crop, weed, texture analysis, classifier DOI: 10.25165/j.ijabe.20201301.4920 Citation: Kamath R, Balachandra M, Prabhu S. Crop and weed discrimination using Laws’ texture masks. Int J Agric & Biol Eng, 2020; 13(1): 191–197.